Βιβλιοκρισία: A. GIANNOULI, Ε. SCHIFFER (εκδ.), From Manuscripts to Books. Proceedings of the Intern. Workshop on Textual Criticism and Editorial Practice for Byzantine Texts (Vienna, 10 – 11 December 2009) , Βιέννη 2011. - ΑΝΤΩΝΟΠΟΫΛΟΥ, Θεοδώρα (Byzantina Symmeikta, 2013)
Βιβλιοκρισία του: A. GIANNOULI, Ε. SCHIFFER (εκδ.), From Manuscripts to Books. Proceedings of the International Workshop on Textual Criticism and Editorial Practice for Byzantine Texts (Vienna, 10 – 11 December 2009) / Vom Codex zur Edition. Akten des internationalen Arbeitstreffens zu Fragen der Textkritik und Editionspraxis byzantinischer Texte (Wien, 10.-11. Dezember 2009) (Österreichische Akademie der Wissenschaften, Philosophisch-historische Klasse, Denkschriften, 431 / Veröffentlichungen zur Byzanzforschung, 29), Βιέννη 2011, σελ. 217. ISBN 978-3-7001-7132-4